Functional significance of morphological variation in the mechanosensory lateral line system of fishes and its biomimetic potential - Ishu Aggarwal; Jacqueline F. Webb; Patrick R. Onck; Ajay Giri Prakash Kottapalli (Proceedings of the National Academy of Sciences, 2026)
The mechanosensory lateral line system, found in all fishes, detects water movement and pressure fields and mediates crucial behaviors in aquatic environments. Neuromast sensory organs, the functional units of the system, exhibit diversity in shape and size among species, but structure–function relationships that could explain this impressive diversity have not been explored. Here, we employ a fluid–structure interaction–based computational model that uses the shape and size of the base of the cupula (the gelatinous cap covering the neuromast) as a proxy for neuromast shape and size. Simulations showed that sensitivity of the cupula (bending response to defined water flows) varies with its shape and size, direction of water flow relative to the major axis of the cupula, as well as with cupula height and material properties (elastic modulus). Sensitivity varied among cupulae with shapes known among superficial neuromasts and canal neuromasts within narrow and widened canals. In addition, predictions made by the model for the sorts of changes in neuromast morphology known to occur during ontogeny predict complex changes in neuromast sensitivity through developmental time. In using variation in cupula responses to flow as a proxy for neuromast responses, this work has revealed an unexplored aspect of adaptive functional evolution in the lateral line system with the potential to inspire the development of biomimetic sensors and robots with applications in industry, medicine, and environmental monitoring and exploration.